The Multi Sectorial Approach to COVID-19 Pandemic in Limited-Resource Settings: Discussing Rwandan Experience - Uwizeyimana, Theogene; Ntacyabukura, Blaise; Damascene Kabakambira, Jean; Shonza, Felicitee; Dushime, Jackson; Humura, Fabrice; Niyonkuru, Samuel; Rukundo, Augustin; Ngenzi, Vivaldi; Tuyishime, Simeon; Ahmed Mohammed Elhadi, Yasir; Manirambona, Emery; et al. (Journal of Public Health International, 2021)
COVID-19 has unprecedentedly shaken the health systems across the globe. Rwanda, a low-income country in East Africa, has succeeded to contain the first wave but is struggling to curb the second wave in the wait for a massive vaccination program. The national committee composed of different ministries and a COVID-19 Joint Task Force was established as a Multi-sectoral approach in the early days of the pandemic. The approach together with transparent communication to the population has been effective. However, much more tailored and cost-effective measures against the drivers of cluster outbreaks are needed to save both the economy and more lives. It is challenging to produce evidence about behaviors attributable to the surge of infections, and their hardship, and how to allow the population to live their lives with less risk. With important research, policymakers will be able to think locally and provide easy and inexpensive recommended behaviors while awaiting the vaccine.
Keywords: C0VID-19; Multi-sectoral interventions; Healthcare system; Rwanda